2002
DOI: 10.1063/1.1481789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of H2 impregnation on excimer-laser-induced oxygen-deficient center formation in synthetic SiO2 glass

Abstract: We examined the effect of H2 impregnation on defect formation upon F2 laser (7.9 eV) and ArF excimer laser (6.4 eV) irradiation. It was revealed that H2 impregnation enhanced the formation of oxygen-deficient center (Si–Si bond) as well as suppressed the formation of E′ center and nonbridging oxygen hole center. A Si–Si bond gives an intense absorption band peaking at 7.6 eV, which contributes the absorption at the wavelength of F2 laser light. These results indicate that H2-free SiO2 glass, which is clearly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In the case of all-silica fiber, gratings can be produced with ArF radiation at 193 nm [13] rather than with 248 nm KrF laser light typically used for Ge-doped fibers. Defect formation after exposure to 193 nm, or even shorter wavelength 157 nm light from a F 2 laser, has been studied primarily in bulk silica glasses, both with and without hydrogen loading [14,17,18]. The results are very similar to what we observe in our studies, i.e.…”
Section: Corning Smf-28 (Ge-doped Core All-silica Cladding)supporting
confidence: 82%
“…In the case of all-silica fiber, gratings can be produced with ArF radiation at 193 nm [13] rather than with 248 nm KrF laser light typically used for Ge-doped fibers. Defect formation after exposure to 193 nm, or even shorter wavelength 157 nm light from a F 2 laser, has been studied primarily in bulk silica glasses, both with and without hydrogen loading [14,17,18]. The results are very similar to what we observe in our studies, i.e.…”
Section: Corning Smf-28 (Ge-doped Core All-silica Cladding)supporting
confidence: 82%
“…This treatment usually increases radiation toughness, e.g., against KrF laser (5.0 eV) irradiation [64]. However, it was found that under irradiation by ArF or F 2 laser photons, H 2 loading indeed helps to suppress the creation of dangling bonds, but at a price of much enhanced generation of oxygen vacancies [24]. The suggested mechanism of this phenomenon is the stabilization of radiation-created oxygen interstitials by transforming them to silanol bonds.…”
Section: Strained Bonds and Role Of Hydrogen And Fluorine Dopantsmentioning
confidence: 98%
“…The 7.6 eV absorption band is important to vacuum UV applications of silica. It is efficiently created by ArF or F 2 excimer laser photons in the presence of interstitial H 2 [24]. Presently the assignment of neutral O vacancy is widely accepted, however, it is also argued that more complex defect structures could be involved [25].…”
Section: Neutral Oxygen Vacancy ("Si-si Bond")mentioning
confidence: 98%
“…It was first loaded with H 2 ($2.5 atm) for 10 h at 500°C to suppress the formation of the silicon and oxygen dangling bonds (E 0 and non-bridging oxygen hole centers, respectively) whose absorption bands ($4-8 eV) interfere with the measurements of VUV absorption band of SiOH groups [7,8]. The sample was then exposed to 7.2 · 10 4 pulses of F 2 laser light (LPF-210, Lambda Physik, hm = 7.9 eV, $6 mJ cm À2 pulse À1 , pulse duration $20 ns) at room temperature, followed by isochronal annealings (10 min) from 100 to 800°C in 100°C steps.…”
Section: Bleaching Of Vuv Absorption Band Of Sioh Groups By Hydrogen mentioning
confidence: 99%